Novel biochar and hydrochar for the adsorption of 2-nitrophenol from aqueous solutions: An approach using the PVSDM model. (April 2021) - Pauletto, P.S.; Moreno-Pérez, J.; Hernández-Hernández, L.E.; Bonilla-Petriciolet, A.; Dotto, G.L.; Salau, N.P.G.
Abstract: Two new adsorbents, namely avocado-based hydrochar and LDH/bone-based biochar, were developed, characterized, and applied for adsorbing 2-nitrophenol. The pore volume and surface diffusion model (PVSDM) was numerically solved for different geometries and applied to interpret the adsorption decay curves. Both adsorbents presented interesting textural and physicochemical characteristics, which achieved maximum adsorption capacities of 761 mg/g for biochar and 562 mg/g for hydrochar. The adsorption equilibrium data were well fitted by Henry isotherm. Besides, thermodynamic investigation revealed endothermic adsorption with the occurrence of electrostatic interactions. PVSDM predicted the adsorption decay curves for different adsorbent geometries at different initial concentrations of 2-nitrophenol. The surface diffusion was the main intraparticle mass transport mechanism. Furthermore, the external mass transfer and surface diffusion coefficients increased with the increase of 2-nitrophenol concentration. Graphical abstract: Image 1 Highlights: Numerical solution of the PVSDM model for different geometries. 2-nitrophenol adsorption onto avocado-based hydrochar and LDH/bone-based biochar. Adsorption capacities were 761 mg/g for biochar and 562 mg/g for hydrochar. 99% of intraparticle transport was controlled by surface diffusion.